2023
DOI: 10.3389/fmed.2023.1130692
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of anatomic vs. non-anatomic resection in intrahepatic cholangiocarcinoma with hepatolithiasis: A multicenter retrospective study

Abstract: BackgroundThe benefits of anatomic resection (AR) vs. non-anatomic resection (NAR) in patients with primary intrahepatic cholangiocarcinoma (ICC) with hepatolithiasis (HICC) are unclear. This study aimed to compare the long-term outcomes of AR vs. NAR in patients with HICC.MethodsA total of 147 consecutive patients with HICC who underwent R0 hepatectomy were included. Overall survival (OS) and recurrence-free survival (RFS) following AR vs. NARs were compared using a 1:1 propensity score matching (PSM) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…A comprehensive literature search was conducted in databases including PubMed, Embase, the Cochrane Library, Medline, and Web of Science to identify relevant studies evaluating the potential benefits of AR for ICC patients. Ultimately, as presented in Supplementary Table 3 , a total of six studies encompassing 1523 patients were included in the analysis [ 13 , 14 , 19 , 31 – 33 ], with 764 patients allocated to the AR group and 759 patients allocated to the NAR group. The findings from five studies collectively indicated a favorable effect of AR on the prognosis of ICC, along with reduced rates of postoperative recurrence [ 13 , 14 , 31 – 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A comprehensive literature search was conducted in databases including PubMed, Embase, the Cochrane Library, Medline, and Web of Science to identify relevant studies evaluating the potential benefits of AR for ICC patients. Ultimately, as presented in Supplementary Table 3 , a total of six studies encompassing 1523 patients were included in the analysis [ 13 , 14 , 19 , 31 – 33 ], with 764 patients allocated to the AR group and 759 patients allocated to the NAR group. The findings from five studies collectively indicated a favorable effect of AR on the prognosis of ICC, along with reduced rates of postoperative recurrence [ 13 , 14 , 31 – 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, as presented in Supplementary Table 3 , a total of six studies encompassing 1523 patients were included in the analysis [ 13 , 14 , 19 , 31 – 33 ], with 764 patients allocated to the AR group and 759 patients allocated to the NAR group. The findings from five studies collectively indicated a favorable effect of AR on the prognosis of ICC, along with reduced rates of postoperative recurrence [ 13 , 14 , 31 – 33 ]. Conversely, the outcomes of the remaining study indicated that the implementation of AR did not yield improvements in prognosis among patients with solitary ICC that lacked direct invasion of adjacent organs or extrahepatic metastases [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations